Environmental dynamics: unraveling the nexus of air pollution, population agglomeration, and sustainable economic development in China: a provincial-level empirical analysis - Yan, Jun; Liu, Chang; Xiao, Bo; Wang, Suzhen (Frontiers in Environmental Science, 2024)
Sustainable economic development is a hot issue in current research, and it is of great significance to analyze the effects of air pollution and population agglomeration on sustainable economic development. This study collects the relevant data released by the Chinese government from 2011–2021, and empirically analyzes the method of constructing an individual one-factor fixed-effects model in order to explore the impacts of SO2 emissions and population agglomeration on sustainable economic development. Through the analysis, it is found that SO2 emissions are negatively correlated with sustainable economic development, and the direction and intensity of its influence are affected by urbanization level, industrial structure, and living standards of residents. The influence of population agglomeration on economic sustainable development is positively correlated. Meanwhile, through the sub-regional study, we further confirmed that the impact of the above influencing factors on the sustainable economic development of different regions is different. Therefore, in order to promote sustainable economic development, it is necessary to further identify the stage of sustainable economic development according to the actual situation of different regions, and to effectively integrate factors including the environment, population, urbanization, industrial structure, etc.